Effect of Quadriceps Strengthening Exercise on Reduction of Pain in Knee Osteoarthritis (Bangladesh Medical Journal, 2014)
Osleoarthritis is the leading cause of musculoskeletal pain and disability. Nonsteroidal anti-inflammatory drugs and physical modalities like Quadriceps muscle strengthening exercise can be used to treat such cases. This Randomized clinical trial study was done in the department of Physical Medicine and Rehabilitation, Sylhet M.A.G Osmani Medical College Hospital Sylhet, lo evaluate the role of quadriceps strengthening exercise in knee osteoarthritis during 1st April 2009 to 3lst October 2009. Sixty patients with knee osteoarthritis were selected according to inclusion and exclusion criteria. They were divided in, group A and group B randomly. Group- A was treated with NSAID (Aceclofenac 100 mg 12hrly) and group-B with NSAID and quadriceps strengthening exercise 10 repetition 3 times daily. Each patient was followed try every week for four weeks. The mean age was 61.067 ± 8.320 years and male female ratio was 1.4:1. Marked improvement was observed in both the groups assessed by pain score (p